Rancang Bangun Pendeteksi Logam pada Conveyor Batubara di Kapal MV WHS Iskandar 1 Berbasis Arduino Uno - Ihzar Haykal; Hadi Setyawan; Dwi Yanti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Worldwide trade is conducted 80% through maritime routes, including the export and import of coal. Coal is a non-renewable energy source, often used as fuel for power plants. As technology advances, detecting metal contaminants in coal cargo becomes crucial to prevent contamination of coal with metal materials. This study aims to (1) understand the operation of a conveyor in transporting coal, and (2) assess how the Proximity inductive sensor detects metal presence. The methods used in this research include real data analysis and literature review, conducted aboard the ship. The researcher designed and developed a prototype system for this purpose. The Proximity inductive sensor is utilized to detect metal contaminants, such as aluminum, iron, and stainless steel, among the coal cargo. The research was carried out during sea practice (prola) aboard the WHS ISKANDAR 1. The findings indicate that the conveyor is driven by a DC motor, and the Proximity inductive sensor effectively detects metals to separate them from the coal cargo, thus purifying the coal from metal contaminants.